Taxation, Bank Leverage, and Financial Crises - Mooij, Ruud A. (IMF Working Papers; Working Paper ;, 2013)
That most corporate tax systems favor debt over equity finance is now widely recognized as, potentially, amplifying risks to financial stability. This paper makes a first attempt to explore, empirically, the link between this tax bias and the probability of financial crisis. It finds that greater tax bias is associated with significantly higher aggregate bank leverage, and that this in turn is associated with a significantly greater chance of crisis. The implication is that tax bias makes crises much more likely, and, conversely, that the welfare gains from policies to alleviate it can be substantial-far greater than previous studies, which have ignored financial stability considerations, suggest.